An Overview of Alphafold's Breakthrough - Marcu, Ştefan-Bogdan; Tăbîrcă, Sabin; Tangney, Mark (Frontiers in Artificial Intelligence, 2022)
This paper presents a short summary of the protein folding problem, what it is and why it is significant. Introduces the CASP competition and how accuracy is measured. Looks at different approaches for solving the problem followed by a review of the current breakthroughs in the field introduced by AlphaFold 1 and AlphaFold 2.